al-ʻAllāmah Abū Isḥāq Aṭfayyish wa-Dawruhu fī Nashr al-Turāth al-ʻUmānī - Rāshidī, Muḥammad ibn Yaḥyá ibn Sufyān (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
This research is concerned with introducing the learned Abū Isḥāq Aṭfayyish and his standing, and examines the ties that bound him to Oman and his role in publishing the Omani heritage through his prefaces and annotations to certain Omani books, and through his writing about parts of the Omani heritage in publications and journals. In addition, the research seeks to set out examples of the heritage in whose publication Abū Isḥāq Aṭfayyish had a part in one form or another. The research aims to bring out his role in publishing Omani works, and likewise to make access to that Omani heritage easier by treating the most important of his works upon it, so that researchers may find in a single place an account of what he edited, annotated and brought into print.
MHF-PRINT2018-017
Keywords: Abū Isḥāq Aṭfayyish; Omani heritage; Publishing; Critical editing; Ibāḍī scholarship; Book history